2015
DOI: 10.1021/bi5008047
|View full text |Cite
|
Sign up to set email alerts
|

Why Does Asn71 Deamidate Faster Than Asn15 in the Enzyme Triosephosphate Isomerase? Answers from Microsecond Molecular Dynamics Simulation and QM/MM Free Energy Calculations

Abstract: Deamidation is the uncatalyzed process by which asparagine or glutamine can be transformed into aspartic acid or glutamic acid, respectively. In its active homodimeric form, mammalian triosephosphate isomerase (TPI) contains two deamidation sites per monomer. Experimental evidence shows that the primary deamidation site (Asn71-Gly72) deamidates faster than the secondary deamidation site (Asn15-Gly16). To evaluate the factors controlling the rates of these two deamidation sites in TPI, we have performed graphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…However, N71 deamidates approximately twofold faster than N15 . Ugur et al . suggested that N71 deamidates faster than N15 not only due to a greater solvent exposure, but also due to higher acidity of the G72 backbone NH group, and increased ability to access reactive conformations conducive to the nucleophilic attack by the backbone nitrogen atom of G72.…”
Section: Prediction Of Chemical Degradation Sitesmentioning
confidence: 99%
“…However, N71 deamidates approximately twofold faster than N15 . Ugur et al . suggested that N71 deamidates faster than N15 not only due to a greater solvent exposure, but also due to higher acidity of the G72 backbone NH group, and increased ability to access reactive conformations conducive to the nucleophilic attack by the backbone nitrogen atom of G72.…”
Section: Prediction Of Chemical Degradation Sitesmentioning
confidence: 99%
“…We show in Figure 2 the average speed (in ps/day) of NVT SEBOMD simulations for different sizes of pure water molecular systems. From left to right, the systems respectively contain 64, 125, 216, or 512 water molecules, encaged in a periodic box with a density of 1.0 g/cm 3 . The D&C algorithm uses 1 water molecule per core, a first buffer of 6Å and no second buffer.…”
Section: Parallel Performancementioning
confidence: 99%
“…A time step of 2.0 fs was used by the implementation of the SHAKE algorithm for the bonds involving hydrogens . The equilibration of the samples was performed in a five stage process . First, after a short 1000 step minimization, a 100 ps molecular dynamics was performed at 10 K with a strong temperature coupling (i.e., velocities were randomly updated every 10 steps in the Andersen thermostat) and with a harmonic restraint of 50 kcal/mol/Å 2 on all nonhydrogen atoms to ensure a proper geometry of the hydrogen atoms that were added by the tLEAP program and to relax the hydrogen bond network between the water molecules and the protein.…”
Section: Computational Detailsmentioning
confidence: 99%